LIFESTYLE PECULIARITIES OF MODERN MYOPIC SCHOOLCHILDREN: A MEDICO-SOCIAL STUDY - M.E. Gurileva; G.G. Galimzyanova ("Paediatrician" Publishers LLC, 2011)
Myopia - is the most common vision defect, that is being formed due to impaired school routine, work and recreation conditions, motion activity and against the background of increased physical and psychological stress. Study objective: study lifestyle peculiarities of myopic schoolchildren. Methods: 349 pupils from 5-9 forms of a school with profound studying of various subjects were interviewed using a specially designed questionnaire. After a preventive examination the schoolchildren were divided into two groups according to ophthalmologists report, comparable by age and gender (162 myopic vs 182 without myopia). Results: all participants were poorly informed about myopia and possible preventive care, and during breaks behaved themselves in an unreasonable way judging from the positions of vision care. At home myopic children tended to spend more time doing their homework and on extracurricular studies, as well as on reading; these children in general spent more time watching TV or working on a computer; failed to rest properly, couldn't switch from one type of activity to another, were working under conditions of unreasonable vision workload. In contrast to participants from control group, myopic schoolchildren spent less time resting: they were sleeping less and spent less time outdoors. Conclusion: revealed lifestyle peculiarities of modern myopic schoolchildren must become a target for preventive care. Their irrational lifestyle can be corrected by correction of daily routine, better organization of extracurricular exercises, visual exercises, better education of schoolchildren about disease risk factors. Key words: schoolchildren, myopia, risk factors. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2011; 10 (4): 5-9)